Improving Students’ English Speaking Skill through Merdeka Belajar- Kampus Merdeka” (MBKM): A Guided Question for Fifth Grade Of SDS Wahidiyah Kediri - Saifuddin, Saifuddin (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study is categorized as a classroom action research (CAR). This study proposed guided questions through inside outside circle as the strategy in the teaching English at the fifth grade students of SDS Wahidiyah Kediri to solve the students’ incompetency on speaking skill. As the result of the preliminary study indicated that the students’ problems toward their speaking competence can be grouped into four problems: (1) lack of vocabularies, (2) the poorness of producing utterances, (3) lack of ideas to speak, and (4) afraid to speak. Therefore, the criteria of success were directed to the mentioned problems. The results showed that by repeating conversations for many times in the activity of guided questions through inside outside circle and also demanding the students to involve actively, the students’ speaking skill improved and the students’ participation in the classroom was highly positive. 70% students gave opinions that the teaching learning activity of speaking using guided questions through inside outside circle strategy.